Tingkat Keterampilan Bermain Bola Voli Pada Unit Kegiatan Mahasiswa Bola Voli Pada Jurusan Olahraga dan Kepelatihan Universitas Jambi: (Volleyball Skill Level In the Volleyball Student Activity Unit In the Sports and Coaching Department Jambi University) - Rasyono, Rasyono; Setiawan, Iwan Budi (Jurusan Pendidikan Olah Raga dan Kepelatihan FKIP Universitas Jambi, 2020)
This research was conducted because the level of volleyball playing skills of the Volleyball Student Activity Unit (UKM) of Sports and Coaching Department was not yet known, therefore this study aims to determine the level of volleyball playing skills of the Volleyball Student Activity Unit (UKM) in the Sports and Coaching Department. This research is a descriptive study, the method used in this research is a survey method with a test instrument. The research subjects were 20 participants of the Volleyball Student Activity Unit, Department of Sports and Coaching. The data collection technique used the upper passing test using the AAHPER face wall volleyball test, the under passing test using the Brumbach forearms pass volleyball test, the smash test using the Stanley spike test, the accuracy test using the AAHPER service accuracy test. The data analysis technique used descriptive percentages. The results showed that of the 20 students who took the volleyball skill level test, 9 students were included in the medium category (45%), 6 students or as many as (30%) were in the good category, as many as 4 students or as much as (20%) were included. Very poor category, as many as 1 student or as large as (5%) are in the very good category, as many as 0 students or as much as (0%) are in the poor category. Abstrak. Penelitian ini dilakukan karena belum diketahuinya tingkat keterampilan bermain bola voli peserta UKM Bolavoli Jurusan Olahraga dan Kepelatihan, maka dari itu penelitian ini bertujuan untuk mengetahui tingkat keterampilan bermain bola voli peserta UKM Bolavoli Jurusan Olahraga dan Kepelatihan. Penelitian ini merupakan penelitian deskriptif, metode yang digunakan dalam penelitian ini adalah metode survei dengan instrumen berupa tes. Subjek penelitian adalah peserta UKM Bolavoli Jurusan Olahraga dan Kepelatihan sebanyak 20 orang. Teknik pengambilan data menggunakan tes passing atas menggunakan AAHPER face wall volleyball test, tes passing bawah menggunakan Brumbach forearms pass volleyball test, tes smash menggunakan stanley spike test, tes ketepatan servis menggunakan tes ketepatan servis AAHPER. Teknik analisis data menggunakan deskriptif dengan persentase. Hasil penelitian menunjukan bahwa dari 20 siswa yang mengikuti tes tingkat keterampilan bola voli, sebanyak 9 siswa termasuk dalam kategori sedang (45%), sebanyak 6 siswa atau sebesar (30%) termasuk kategori baik, sebanyak 4 siswa atau sebesar (20%) termasuk kategori sangat kurang, sebanyak 1 siswa atau sebesar (5%) termasuk kategori sangat baik, sebanyak 0 siswa atau sebesar (0%) termasuk kategori kurang.